POLITIK HUKUM DAN PEMBANGUNAN SISTEM HUKUM PIDANA INDONESIA - Sumartini, Siti (Yustitia, 2013)
The development of Indonesian law is an actualization of the existence of state law (the Rule of Law) as it also is an effort to build a fully human Indonesia, where the development of this law will not be separated from the political role of the law that gives the direction of our legal system will run. Development law also should not change in the structure of society and the changing times. Therefore good law is the law that can respond to the needs of society, therefore the law can also be referred to as a means of social engineering (law ​​as a tool of social engineering) In practice forming an act that will be made, not only should pay attention to legal policies will but are also very important to note in this case the elements forming an act, which the constituent elements are matters relating to the principles of both the formal principle of the form of the draft law and the principles of material concerning the content or substance of the act and then the foundations up to the charge material will be described in the act. Thus benefit from the establishment of the law can be felt by all the people of Indonesia also in this case do not ignore this aspect of the rule of law itself, which is a function of the formation of a law.